Determinants of exchange rate towards export in selected countries / Nurul Shakinah Hilme - Hilme, Nurul Shakinah (2020)
This research is to study the determinants of exchange rate towards export in selected countries such as Malaysia, Japan, Thailand, China, India, Singapore and Indonesia. whereby there is another factor involve GDP rate, exchange rate and inflation rate. Moreover, this study is to identify which one of the independent variables chosen that have most significant impact towards export. The reason of this study is undertaken is because the declining trend of data in export sector due to declining in exchange rate. It became a worrisome to Malaysia economy growth. Even though the declining in export are not seeing the effects directly to the balance of trade or economic growth but currently now government more spending than earning. In this study where GDP rate, inflation rate and exchange rate are independent variables and export rate as the dependent variable. This paper literally shows on the significant determinants of exchange rate towards export. In this study, the software used is E-views to diagnose the data from year 1988-2018, the data collected from World Bank Data and Macroeconomic, analyse the Unit root-test and Granger Causality. Turn out the result are significant between the variable export rate and exchange rate, inflate rate shows insignificant determinants of exchange rate towards the changes of export rate.